2004
DOI: 10.1063/1.1773551
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the impact of an ink-jet printed droplet on a solid substrate

Abstract: This paper reports on an experimental study of the impact of water droplets on a solid substrate, with a droplet radius between 18 and 42 μm. We optically measured the interface shape during impact. The measured impact sequences show the impact phenomenology, droplet radius as a function of time, and oscillation behavior in the later stages of impact. The measured radius during impact is compared with existing models, and some of the deficiencies of common models are shown. The measured oscillation frequency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(213 citation statements)
references
References 27 publications
10
192
1
10
Order By: Relevance
“…III. Equation (53) shows good agreement with the trends shown and the limited measured bubble volumes in the experiments for droplet impact with a solid, 3,4 with the volume of the gas bubble trapped increasing with bubble radius and decreasing with impact speed. 18 Very limited experimental results exist which allow comparison of the bubble volume with the liquid layer depth.…”
Section: Trapped Bubble Sizesupporting
confidence: 73%
See 1 more Smart Citation
“…III. Equation (53) shows good agreement with the trends shown and the limited measured bubble volumes in the experiments for droplet impact with a solid, 3,4 with the volume of the gas bubble trapped increasing with bubble radius and decreasing with impact speed. 18 Very limited experimental results exist which allow comparison of the bubble volume with the liquid layer depth.…”
Section: Trapped Bubble Sizesupporting
confidence: 73%
“…2 In addition to bubbles trapped by air cushioning between a droplet and a liquid layer, experimental studies have also shown that gas bubbles can be created as the result of air cushioning during droplet impact with a rigid surface. 3,4 In air-cushioned droplet impact experiments, in addition to the large central bubble, much smaller bubbles have also been seen at a greater radius from the center of the impact in a phenomena called Mesler entrainment. 5,6 This is inferred to be the result of capillary interactions between the droplet and liquid layer free-surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually the decelerated droplet free-surface directly below the centre of the droplet is overtaken by the surrounding free surface, with the pressure profiles similarly bifurcating to produce maxima where the separation between free surface and substrate are least. Touchdown then goes on to occur around a ring some horizontal distance away from the point directly below the centre of an air bubble, leading to a trapped pocket of gas, which subsequently may evolve to form a bubble, as observed in experiments [4,6,38]. In a vacuum, the initial touchdown would occur at time t = 0.…”
Section: Gas Behaviour In the Substratementioning
confidence: 95%
“…Most studies on low-speed droplet impact focus on the spreading and splashing of droplets. 6,7 Surprisingly, the field between high-speed and low-speed droplet impact ͑i.e., velocities between 20 m and 150 m/s͒ did not receive much attention in the past.…”
Section: Introductionmentioning
confidence: 99%